(3YOI GdMUf GdMUjf ef cdGe SjO GdeQSdjfs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , (B833 (3g` s ((3EHQGgje Hf jhSa GdOGeQGfj GdTGaYjs)
(3ChdgG (B:s
(3bGdGHf MLQ GdYSbdGfjbGdeMeO Hf eMeOGdLRQj GdTGaYjGdMeO ddg GdPj LYd PcQg YOI dMUf GdMUjfhHYO adeG cGf cJGH MUf GdMUjf ef cdGe SjO GdeQSdjf MOGfj Ydi GNJUGQgs
(3BNQgG (B:s
(3hYQV Hjf GdfaS hGdghi hGdTjWGf ceG hQO aj GdNjQ Gddge EfG fSCdc GdYGajI aj GdOfjG hGdBNQI hdjcf Pdc BNQ eG fYhP aj YOI GdMUf GdMUjfs
(3aj Chdg JYdjb HNW LeGd GdOjf Hf eMeO Hf CHj HcQ UGdM, GdTgjQ HCHj GdNjGW Gdjefj, haj Chdg bQGAI Ydi GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 45s
(3eYLe GdeDdajf(B: 3 / 687s
(3cTa GdXfhf(B: 1 / 670s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs